The Effect of Inositol On Malondialdehyde Serum Levels in Medical Students With PCOS - Eldisha Nofityari; Mondale Saputra; Hirowati Ali (Andalas Obstetrics And Gynecology Journal, 2026)
Introduction: Polycystic ovary syndrome involves the endocrine system, metabolic system, as well as the reproductive system contributing to anovulatory infertility. Polycystic ovary syndrome affects 5-20% of reproductive age and 6-12% of adolescents. Oxidative stress is known to play an important role in the pathogenesis of PCOS resulting in excessive formation of ROS (malondialdehyde). ROS can be controlled by the antioxidant inositol and has minimal side effects.  To determine the effectivity of inositol antioxidant on malondialdehyde serum levels in female students Medical faculty, Andalas University with clinical PCOS. Methods: This study is a clinical trial research with a pure experimental study design (true experimental design). There were 23 samples for the experimental group and 23 samples for the control group selected by probability sampling. Normality test using Shapiro-Wilk test. Data analysis using Independent T test and Mann Whitney Test. Results: There was a significant decrease in malondialdehyde serum levels in PCOS students who consumed inositol therapy for 3 months. Conclusion: There is an effect of inositol antioxidant consumption on malondialdehyde serum levels in female students Medical faculty, Andalas University with clinical polycystic ovary syndrome.